Networking: a study in planning and developing cross-cultural collaboration - Sanjeev Singh; Jon Dron (Association for Learning Technology, 2002)
This paper reports on a collaboration between the authors at the University of Brighton (UK) and the University of Delhi, South Campus. The collaboration came about as a result of the EU-India Cross-Cultural Innovation Network collaboration programme, a project involving several universities and organizations across Europe and India. The authors of this paper both lecture in the area of computer networking. Following meetings in Delhi, they agreed to work together to produce a Web-based networking resource to be generated by the students of both institutions. The first phase of development involved the mounting of Web-based tutorials and documents produced by the students. The second phase will centre on the development of a knowledge base generated by the interaction of the students within an asynchronous forum. Running alongside these phases will be a collaborative bookmarking system, a database in which the students will post URLs of Web-based resources that they find useful in their studies. This system incorporates a form of collaborative filtering, an evolutionary mechanism which seeks to embody the qualities that students value in resources to provide a dynamic set of ratings to assist in the selection of those of most use. The planning of such a system raises some unusual issues, not least in the process of collaboration itself, with concerns as diverse as technical compatibility, institutional and cultural differences, timezones and the reliability of email. Limited bandwidth between our institutions causes special problems with the interactive elements of the resource. We present the methods we are investigating to reduce the impact of this. The fact that the students share an intellectual discipline but are otherwise separated by a cultural and geographical divide is expected to lead to fruitful diversity in thinking and approaches to problem-solving.